2021
DOI: 10.1021/acs.chemrestox.0c00336
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Prediction of Input Parameters for Simplified Physiologically Based Pharmacokinetic Models for Estimating Plasma, Liver, and Kidney Exposures in Rats after Oral Doses of 246 Disparate Chemicals

Abstract: Recently developed computational models can estimate plasma, hepatic, and renal concentrations of industrial chemicals in rats. Typically, the input parameter values (i.e., the absorption rate constant, volume of systemic circulation, and hepatic intrinsic clearance) for simplified physiologically based pharmacokinetic (PBPK) model systems are calculated to give the best fit to measured or reported in vivo blood substance concentration values in animals. The purpose of the present study was to estimate in sili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 28 publications
(84 reference statements)
1
50
0
Order By: Relevance
“…In this study, neopetasitenine and its deacetylated metabo-lite petasitenine were selected as model substances. The previously reported in silico machine learning system (Kamiya et al, 2021) yielded important pharmacokinetic parameters (k a , V 1 , and CL h,int ) of neopetasitenine and petasitenine based on their chemical descriptors (Table 1). This approach was used because of the absence of experimental pharmacokinetic data in rats.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, neopetasitenine and its deacetylated metabo-lite petasitenine were selected as model substances. The previously reported in silico machine learning system (Kamiya et al, 2021) yielded important pharmacokinetic parameters (k a , V 1 , and CL h,int ) of neopetasitenine and petasitenine based on their chemical descriptors (Table 1). This approach was used because of the absence of experimental pharmacokinetic data in rats.…”
Section: Resultsmentioning
confidence: 99%
“…Pharma- (Kamiya et al, 2020b); the value in parentheses was determined experimentally and confirmed after the in silico estimation. b Initial values for PBPK modeling for the absorption rate constant (k a ), volume of the systemic circulation (V 1 ), and hepatic intrinsic clearance (CL h,int ) were estimated by in silico machine learning methods with a dataset of 246 chemicals, as described previously (Kamiya et al, 2021). cokinetic parameters such as k a , the apparent volume of distribution (V/F), and the oral clearance (CL) were preliminary calculated for neopetasitenine and petasitenine using one-compartment models (Table 2), based on the rat plasma data obtained in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A simplified rat PBPK model consisting of chemical receptor (gut), metabolizing (liver), excreting (kidney), and central compartments was set up as described elsewhere (Kamiya et al, 2020b(Kamiya et al, , 2021. The molecular weights (258, 274, and 274), octanol-water partition coefficients (clogP; 0.528, -0.138, and 0.402), plasma unbound fractions (f u,p ; 0.588, 0.615, and 0.237), and blood-plasma concentration ratios (R b ; 0.893, 0.885, and 0.904) of thalidomide, 5′-hydroxythalidomide, and 5-hydroxythalidomide, respectively, were used as described previously (Nishiyama et al, 2015;Yamazaki et al, 2012).…”
Section: Estimation Of Rat Plasma Concentrations Using Physiologically Based Pharmacokinetic Modelmentioning
confidence: 99%
“…20) The input parameters for PBPK models are generally based on in vivo data; however, to investigate the feasibility of making such modeling more accessible in real-time, we generated PBPK model input parameters in silico for a broad range of chemicals using a machine learning algorithm without reference to in vivo studies. 21,22) The values of the three major PBPK model input parameters, i.e., the absorption rate constant (k a ), the volume of the systemic circulation (V 1 ), and the hepatic intrinsic clearance (CL h,int ), for this selection of chemicals were previously generated in silico for rats. 21) Therefore, the aim of the present study was to establish in silico models for predicting k a , V 1 , and CL h,int values (for use in human PBPK models) based on a number of chemical descriptors.…”
Section: Introductionmentioning
confidence: 99%